Սոցիալական աշխատանքը և հետխորհրդային Հայաստանի բնակչության սոցիալական պաշտպանության համակարգը - Խաչատրյան, Արտակ (Bulletin of Yerevan University G: Economics, 2017)
The article analyzes the influence of social work on the social protection system of the Armenian society of the post-Soviet period. The author justifies the view that introducing social work into the social protection system of the Armenian society will dramatically increase the effectiveness of the system by increasing the targeting of social services, transforming the process of providing social services with professional activities.
Keywords: system of social protection, social work, social risk, social support